1952
DOI: 10.1002/jcp.1030400212
|View full text |Cite
|
Sign up to set email alerts
|

The relation between ribonucleic acid and ionic transport across the cell surface

Abstract: TWO BIQURESExploratory studies (Lansing, Rosenthal and Kamen, '49) have indicated a n association between a ribonucleoprotein complex and the cell surface. Neuberg and Roberts ('49) have proposed a mechanism for the transport of insoluble inorganic compounds from the soil into roots based upon the remarkable powers of nucleic acids and their derivatives to form complexes with other substances. It occurred to us that a process similar to that described by Neuberg and Roberts could transport ionizable material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1953
1953
1973
1973

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…More recently Ormrod and Williams (29) have shown that 2,4-D treatment causes a rapid rise in soluble organic phosphates, suggesting an increase in such compounds as ATP (since inorganic phosphate is usually incorporated into organic compounds via oxi(lative phosphorylation). RNA is apparently involved in such processes as protein synthesis (3), oxidlative phosphorylation (12), and ion absorption (19,38), processes known to be affected by 2,4-D (9, 16, 28, 35, & 37). Soluble nucleotides are involvedl in such essential biological processes as oxidative phosphorylation (20), amino aci(d metabolism (8), carbohydrate transformations (14), and lipide syntheses (15).…”
mentioning
confidence: 99%
“…More recently Ormrod and Williams (29) have shown that 2,4-D treatment causes a rapid rise in soluble organic phosphates, suggesting an increase in such compounds as ATP (since inorganic phosphate is usually incorporated into organic compounds via oxi(lative phosphorylation). RNA is apparently involved in such processes as protein synthesis (3), oxidlative phosphorylation (12), and ion absorption (19,38), processes known to be affected by 2,4-D (9, 16, 28, 35, & 37). Soluble nucleotides are involvedl in such essential biological processes as oxidative phosphorylation (20), amino aci(d metabolism (8), carbohydrate transformations (14), and lipide syntheses (15).…”
mentioning
confidence: 99%
“…Overstreet and Jacobsen (11) have reviewed the various binding compounds proposed and have listed several characteristics which these compounds should have to fit into any working model of ion uptake. The recent proposal of Lansing and Rosenthal (7) identifying ribonucleic acid as a binding compound in Elodea cells has opened up several possible lines of investigation to test the role of nucleic acids in salt absorption by roots. One of these is the effect on salt absorption of ultraviolet radiation in the wavelength region of 2600 A where there is strong absorption by nucleic acids.…”
mentioning
confidence: 99%
“…Concerning this, it is important to point out that liver and kidney (nonmalignant) from Ehrlich ascites-bearing animals present the highest phospholipid and RNA level in the microsomal fraction. Now, if we consider that the cell membranes (main constituent of the microsomal fraction) are formed by phospholipids (the most important calcium-binding molecules (24] and RNA [31], it is possible that under high-calcification conditions these molecules can undergo the specificgravity changes mentioned above and, as a result, separate with another differential centrifugation fraction. This could be the case of the high RNA and phospholipid in the nuclear fraction of Ehrlich ascites cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is evidence that phos pholipids may be involved in calcification at sites of primary mineralization [25,26], The more recently reported finding of posphate-enhanced Ca2+ binding by acidic phospholipids and the formation of a phospholipidcalcium-phosphate complex [27], together with the increased calcium binding to tumor cell membranes [28], emphasizes the probable role of phospholipids in tumor calcification. In addition, RNA is known to pre cipitate Ca2+ [29,30], and the existence of a thin layer of RNA at the cell surface has been related to an ionic transport function [31]. The protein participation in the cell calcium-binding is believed to be carried out by soluble complexes which are very susceptible to the effects of ionic changes in the cell medium.…”
Section: Introductionmentioning
confidence: 99%